The Effects of Velvet Antler of Deer on Cardiac Functions of Rats with Heart Failure following Myocardial Infarction. (24th April 2012) - Shao, Ming-Jing; Wang, Shuo-Ren; Zhao, Ming-Jing; Lv, Xi-Ling; Xu, Hao; Li, Lin; Gu, Huan; Zhang, Jiu-Liang; Li, Ge; Cui, Xiang-Ning; Huang, Li
Abstract : Velvet antler of deer (VAD) is a commonly-used kidney-Yang supplementing traditional Chinese medication. According to the heart-kidney-related theory, heart Yang originates in kidney Yang and heart failure due to heart Yang deficiency can be treated by tonifying kidney Yang. In this study, we investigated therapeutic effects of VAD on cardiac functions in rats with heart failure following myocardial infarction. Forty-eight male Wistar rats were subjected either to left coronary artery ligation (N = 36 ) or to sham operation (N = 12 ). One week after the surgery, rats with heart failure received daily treatment of double-distilled water, captopril or VAD by gavage for consecutively four weeks, while sham-operated animals were given double-distilled water. Ultrasonic echocardiography was adopted to examine cardiac structural and functional parameters and serum brain natriuretic peptide (BNP) concentration was measured using radioimmunoassay. We found that VAD partially reversed changes in cardiac functional parameters and serum BNP levels in rats with heart failure. These results provide further evidence for the heart-kidney-related theory and suggest that VAD might be a potentially alternative and complementary medicine for the treatment of heart failure.